Assessing the Taxonomic Diversity of Danionid Fishes of Brahmaputra Basin, Assam, North-East India: An Effort towards the Conservation of Small Indigenous Fish - Barman, Manabjyoti; Bhushan, Shashi; Phukan, Bipul; Kumar, Annam Pavan; Jaiswar, Ashok Kumar; Talukdar, Avinash; Kalita, Rinku (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The family Danionidae (Order: Cypriniformes) exhibits a wide diversity with 364 species belonging to 39 genera, most of which are small and brightly coloured and are considered as small indigenous fish. Although, they don’t contribute significantly to the commercial landing, they possess a huge potential for ornamental use, recreational activity apart from food value. Thus to know this potential, a study was taken up to explore the danionid diversity of Brahmaputra basin of Assam, North east India. Fish samples from four different rivers of Brahmaputra basin was collected during 2023, identified through classical taxonomy and preserved in formalin (10%). A total of 17 species belonging to 11 genera and 4 subfamilies were recorded. The subfamily Chedrinae is comprised highest number of species (9), followed by Danioninae (5), Rasborinae (2) and Esominae (1). The present communication deals with the diagnostic characters and colour pattern of the danionid fishes. Findings of the study will help to identify the danionid fishes and thus, conservation of these resources from Brahmaputra River basin of Assam.